Increasing lowland rice yields of smallholder farmers through the adoption of good agricultural practices in the forest agro-ecological zone of Ghana - Ayamba, Benedicta Essel; Buri, Mohammed Moro; Sekyi-Annan, Ephraim; Devkota, Krishna; Dossou-Yovo, Elliott Ronald; Ulzen, Ophelia Osei; Adjei, Eric Owusu; Musah, Mohammed; Biney, Nathaniel (Taylor & Francis Group, 2023)
Rice is an important food crop in Ghana. However, its production has constantly been below 40% of the demand, and most of the requirements meet from imports. Such low production level is largely attributed to farmers’ sub-optimal crop and water management practices. As an effort toward sustainably improving rice yield, three-season on-farm participatory experiments were conducted within the Biem watershed in Ghana to determine the potential of good agricultural practices (GAP) for closing the rice yield gap with agronomic and economic sustainability. Good agricultural practices were compared with 23 farmers’ traditional practices on lowland rice growth and yield, profitability, and nutrient use efficiency. The effect of alternate wetting and drying (AWD) with GAP on grain yield of rice was also determined. Rice yield was on average 28% higher under GAP than farmers’ practices (FP). Alternate wetting and drying did not have significant effect on rice yield when compared to continuous flooding. However, when GAP was combined with AWD, rice yield was 13% higher than under FP. Furthermore, the results of the study indicate that major gains in nitrogen use efficiency (+1.48 kg grain kg−1 N; +2.4%), and net profit (+694.35 USD ha−1; +59%) were achievable through the adoption of GAP. There is therefore, a high potential to close the lowland rice yield gap and achieve rice self-sufficiency through the adoption of GAP in the lowlands of the Inland valley of Ghana and similar rice production regions of West Africa